THE MATHEMATICAL CONSTANTS e AND π: INSIGHTS INTO THEIR SIGNIFICANCE AND APPLICATIONS - Alijonov Sirojiddin Husan ugli; Khabibullaev Sherozbek Khamidulla ugli (American Journals, 2024)
This scientific article explores two of the most significant mathematical constants: e and π. The constant e, also known as Euler's number, and the constant π, denoting the ratio of a circle's circumference to its diameter, play critical roles in various mathematical disciplines. This article delves into the historical background, mathematical properties, and practical applications of e and π, emphasizing their importance in calculus, number theory, geometry, and other areas of mathematics.
Keywords: E, Euler's number, π, pi, mathematical constants, calculus, number theory, geometry, applications, exponential functions, trigonometry, theoretical significance.